Kemunduran Demokrasi Dimulai Dari Kotak Suara - Azizah, Faiqah Nur (BULETIN ADALAH, 2024)
The path to democratic breakdown is often deceptive. It is important to remain vigilant against these threats and to work to protect the integrity of democratic institutions. Rather than relying on overt methods such as coups or violent attacks on government officials, those seeking to undermine democracy may use more subtle tactics. These can include questioning the validity of the constitution or spreading misinformation about the government. Even the Constitution and other institutions with a constitutional label will continue to exist, and people can still vote. Democracy can be undermined by leaders who maintain the appearance of democracy while eliminating its substance. Therefore, the people, as the highest authority in a democratic system, must make efforts to preserve democracy. The progress and setbacks of democracy hinge on the ballot box, where voters critically evaluate the ideas of prospective leaders who will govern the country for the next five years. The progress and setbacks of democracy hinge on the ballot box, where voters critically evaluate the ideas of prospective leaders who will govern the country for the next five years. The progress and setbacks of democracy hinge on the ballot box, where voters critically evaluate the ideas of prospective leaders who will govern the country for the next five years. Therefore, it is crucial for voters to be aware of their responsibility in determining the future leader of the country.